CURRENT STATUS OF COCONUT RESEARCH IN SRI LANKA - RANJITH MAHINDAPALA (International Coconut Community Journal, 1991)
Coconut occupies about 410,000 ha of land in Sri Lanka, and is the largest plantation crop. The most important coconut growing area is called the "Coconut triangle" which comprises most of the districts of Puttalam. Colombo and Gampaha. Together, they account for nearly 70 per cent of the coconut lands. There are about 700,000 coconut growers, the majority of which are small‑holders. About 70‑75 per cent of the holdings are below 4 hectares.